2020
DOI: 10.1128/msystems.00522-20
|View full text |Cite
|
Sign up to set email alerts
|

Fermented-Food Metagenomics Reveals Substrate-Associated Differences in Taxonomy and Health-Associated and Antibiotic Resistance Determinants

Abstract: Fermented foods have been the focus of ever greater interest as a consequence of purported health benefits. Indeed, it has been suggested that consumption of these foods helps to address the negative consequences of “industrialization” of the human gut microbiota in Western society. However, as the mechanisms via which the microbes in fermented foods improve health are not understood, it is necessary to develop an understanding of the composition and functionality of the fermented-food microbiota to better har… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
89
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(94 citation statements)
references
References 97 publications
(110 reference statements)
5
89
0
Order By: Relevance
“…These results suggest that the type of raw food material and the fermentation environment in these regions may impact bacterial richness but not the diversity. Similar findings have been previously reported in other types of fermented food products [51][52][53].…”
Section: Comparison Of Bacterial Communities During the Fermentation Processsupporting
confidence: 92%
“…These results suggest that the type of raw food material and the fermentation environment in these regions may impact bacterial richness but not the diversity. Similar findings have been previously reported in other types of fermented food products [51][52][53].…”
Section: Comparison Of Bacterial Communities During the Fermentation Processsupporting
confidence: 92%
“…LAB strains extracted from sauerkraut have been shown to adhere to CaCo-2 cells and exert antibacterial activity against potential pathogens ( Beganović et al, 2014 ). Leech et al (2020) recently found that the microbial diversity of tibicos and sauerkraut far exceeded that of dairy-based ferments, as well as containing the largest numbers of potential health-promoting gene clusters. As such, tibicos, and sauerkraut were chosen for our study.…”
Section: Introductionmentioning
confidence: 99%
“…A holistic view of the biodiversity of bacterial and phage species of fermented foods is now achievable through a combination of metagenomic and virome analyses. Recently, metagenomic analysis of a range of fermented foods established that the substrate type is a major driver of the ecological diversity ( 14 ), which in turn will impact the phage population composition and dynamics. Virome studies of fermented foods are limited to date and represent a promising and informative alternative/complement to traditional phage screening studies to uncover the full extent of phage biodiversity and the emergence of novel phage species that may threaten food production systems ( Fig.…”
Section: The “Phage Problem”mentioning
confidence: 99%